2018
DOI: 10.1142/s0219887818400042
|View full text |Cite
|
Sign up to set email alerts
|

Chirality in gravitational and electromagnetic interactions with matter

Abstract: It has been suggested that single and double jets observed emanating from certain astrophysical objects may have a purely gravitational origin. We discuss new classes of pulsed gravitational wave solutions to the equation for perturbations of Ricci-flat spacetimes around Minkowski metrics, as models for the genesis of such phenomena. We discuss how these solutions are motivated by the analytic structure of spatially compact finite energy pulse solutions of the source-free Maxwell equations generated from compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…for any complex 0-form α ∈ ΓΛ 0 M. A direct computation now verifies that if α is the complex pulse solution (19) satisfying…”
Section: Spinor Pre-potentialsmentioning
confidence: 63%
See 3 more Smart Citations
“…for any complex 0-form α ∈ ΓΛ 0 M. A direct computation now verifies that if α is the complex pulse solution (19) satisfying…”
Section: Spinor Pre-potentialsmentioning
confidence: 63%
“…It has been suggested that gravitation may also play a role in initiating such processes [18]. We have suggested in [19,17] that an analysis of the timelike geodesics associated with a propagating, gravitational chiral pulse may provide some insight into the relevance of gravitational chirality in initiating the magnetohydrodynamic mechanism. As we shall show, chiral pulses can be shown to account for both uni-directional and bi-directional jet structures.…”
Section: Gravitational Pulses In Vacuamentioning
confidence: 97%
See 2 more Smart Citations
“…With respect to the set of fiducial observers that are all at rest in space, timelike geodesics in such spacetimes generally line up at late times in the direction of wave propagation with Lorentz factors that asymptotically tend to infinity. This cosmic jet feature of plane gravitational waves has been the subject of previous investigations [10][11][12][13].…”
Section: A Principal Null Directionsmentioning
confidence: 74%